Psychiatric Comorbidities in Adult Survivors of Major Trauma: Findings From the Midland Trauma Registry - Spijker, EE; Jones, K; Duijff, JW; Smith, A; Christey, GR (CSIRO, 2018)
INTRODUCTION: Information for primary care providers about the outcomes of adult survivors of major medical trauma in the first year of recovery is not widely available. In particular, risks of impairment across multiple domains of functioning are poorly understood. AIM: To determine the extent to which adults' experience impaired health-related quality of life (QoL), symptoms of post-traumatic stress disorder, depression, chronic pain and harmful alcohol use during the year following major trauma, and to identify factors associated with outcomes. METHODS: Adults (aged ≥16 years) admitted to Waikato Hospital following major trauma sustained in Waikato District between 1 June 2010 and 1 July 2011 were sent a questionnaire in their first year of recovery. They were asked about their QoL, mental health, experiences of pain, post-traumatic stress disorder symptoms and use of alcohol. RESULTS: Sixty-five questionnaires were completed (40% response rate). In the year following major trauma, trauma survivors met criteria for post-traumatic stress disorder (45%), harmful alcohol use (26%), moderate to severe chronic pain (23%) and depression (18%). Reports of poor health-related QoL were common, ranging from self-care difficulties (31%) to pain and discomfort (72%). Younger age, previous psychiatric illness, substance use, intensive care unit admission and length of hospitalisation were associated with symptoms. Thirty-seven adults (57%) reported symptoms in at least two domains. DISCUSSION: A significant proportion of adults experience adverse psychosocial outcomes in the first year following major trauma. Screening and management of potentially comorbid psychosocial needs could improve care and outcomes for survivors.